Identifikasi komposisi unsur logam berat pada lindi tempat pemrosesan akhir (TPA) sampah Kota Padang menggunakan X – Ray Fluorescence (XRF) (Identification of the composition of heavy metal elements in the leachate of Padang City waste final processing site using X-Ray Fluorescence (XRF) - Iswandi Iswandi; - Mahrizal; Fatni Mufit (Department of Physics – Universitas Negeri Padang UNP, 2015)
Final waste processing site of Padang City is located on Air dingin, Kelurahan Balai Gadang, Koto Tangah Sub – distrik has 8 leachate holding pond. At 8 leachate holding pond flowe in to river next to final processing site. Most of residents around the final processing site use water fromriver and well around waste processing site as a source of clean water for daily life. This research aims to know composition ofheavy metal in sedimen of leachate pond, river sediment and gutter sediment of final waste processing site Air Dingin, Padang City. The sample used in this research are 4 samples of leachate pond sediment, 1 sample of gutter, 1 sample of riversediment which have been measured magnetic susceptibility values. The measurement result XRF will show content of elements contained in the samples. Determining the content of heavy metal using determined by matched measurement result with periodic table. The measurement result using XRF further made in to table and graph. The measurement result using XRF show that heavy metal contained insample of leachate pond sediment are Titanium (Ti), Vanadium ( V), Cromium ( Cr ), Manganese ( Mn ), Iron ( Fe ), Cobalt ( Co ), Zinc ( Zn ), Rhadium ( Rh ), Neodinium ( Nd ), Eopium ( Eu ), Iterbium ( Yb ), Indium ( In ) and Zirconium (Zr). At measurement composition of sediment sample is acquired that heavy metal similar to result of leachate sample measurement, only Iterbium (Yb), Indium (In) not foynd, where as on sediment sample of gutter also there is heavy metal that similar to composition sample of leachate and only Indium (In) not found. The heavy metal that dominant find on sample as leachate sediment, river sediment, and gutter sediment is iron with percentage 33.664 % and rhadium with percentage 30.587 %. Heavy metal at final waste processing site Air Dingin suppose get in through metallic waste, chemical waste such as vehicles waste, waste of iron and steel, battery alectric devices, insecticide residuethat not classified weel. When wastes polish by water which get in to final waste processing site, water result of waste degradation sediment at mound of waste and flow to leachate holding wast